2015
DOI: 10.1007/s10894-015-9847-1
|View full text |Cite
|
Sign up to set email alerts
|

Tritium Breeding Ratio Calculation for ITER Tokamak Using Developed Helium Cooled Pebble Bed Blanket (HCPB)

Abstract: In this paper, neutronic calculations were performed to obtain tritium breeding ratio (TBR) for ITER device using developed helium cooled pebble (HCPB) blanket. The designed blanket module has the following combinations; natural lithium, Li 4 SiO 4 (20 %), beryllium moderator and neutron multiplier. To ensure tritium selfsufficiency, the calculated achievable TBR should be equal to or greater than the required TBR. Simulations have been performed by means of Monte Carlo MCNP-4C code using END/B-VII.1 data libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…It will be shown that when the electrical charges come from the process of radioactive decay, i.e. alpha or beta decay, it is possible to extend the Rayleigh limit of charge density, and an expression is derived for the critical size of the bubbles, which can be used to predict the maximum size of tritium bubbles from the coalescence and growth process in liquid Pb-16Li blankets for its extraction in fusion reactor technologies [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…It will be shown that when the electrical charges come from the process of radioactive decay, i.e. alpha or beta decay, it is possible to extend the Rayleigh limit of charge density, and an expression is derived for the critical size of the bubbles, which can be used to predict the maximum size of tritium bubbles from the coalescence and growth process in liquid Pb-16Li blankets for its extraction in fusion reactor technologies [2,3].…”
Section: Introductionmentioning
confidence: 99%